ANALISIS DAMPAK PENGANGGURAN, INDEKS PEMBANGUNAN MANUSIA, ZAKAT DAN PDRB TERHADAP KEMISKINAN DI PROVINSI ACEH - Ahmad Briezy Baihaqi; Maria Puspitasari (Universitas Halu Oleo, 2020)
Poverty, which is closely related to welfare, is one of national resilience scopes. National resilience guarantees the survival of the nation's life which is manifested through citizens' tough living conditions based on trigatra and pancagatra. Based on BPS Indonesia data, the Aceh's poor population percentage in 2007-2014 has always been above the national average and among the top ten provinces with the highest poverty rates in Indonesia. This study aims to determine the effect of the Unemployment Rate, HDI, ZIS; and GRDP per capita with oil and gas to the Poor Population Percentage in Aceh Province in 2009-2015. Using quantitative approach with panel data regression, results of the FEM processed with EViews 9 shows four independent variables have simultaneous and partial significant effect with an adjusted R-squared value of 95.11%. Every increase in Unemployment, ZIS and GRDP per capita by 1% will decrease the Poor Population Percentage. Every increase in HDI will increase the Percentage of Poor Population. Recommendations from the results of this study are that Aceh government should focus on poverty alleviation programs in rural areas in accordance with the 2008 BRR NAD-Nias report and also needs find a one-stop zakat mechanism so the potential of ZIS in Aceh Province can be realized as maximum as possible.